EDUCATIONAL BUILDING PERFORMANCE EVALUATION PRACTICES AND PERCEPTIONS: A CASE OF FEDERAL UNIVERSITIES IN SOUTH EAST NIGERIA - K.C Okolie; W.M. Shakantu (Journal of Construction Project Management and Innovation)
This paper assesses the level of awareness, perception and practice of Building Performance Evaluation (BPE) in the management of educational buildings. Hitherto performance evaluation of buildings has not received significant attention in Nigerian Universities. Universities procure buildings that neither respond to the demands of changing needs, nor fit for purpose. This study relies on current literature to explore how the constructs of BPE can be utilized to improve the design and management of educational buildings in the Nigerian university system. Data were generated using a convenient sample of construction professionals holding key positions in the physical planning and works departments of four Federal Universities in South East Nigeria. Data analyses were conducted using Excel and statistica; Version 9.0. The findings suggest that there appears to be an apparent lack of a systematic mechanism for measuring the success or performance of completed and occupied buildings in the universities. The absence of a performance evaluation database in the institutions explains this situation. The study reveals inadequate funding and lack of skilled personnel to conduct the performance evaluation of buildings. Consequently, the interaction between users and buildings did not add value to learning and working experiences. The paper concludes that a significant number of buildings in the case organisations were not fit for purpose. Furthermore, building performance indicators/measures identified as specific design objectives seem not have been explicitly expressed in most of the buildings investigated. The study emphasizes the need for designers and facilities managers to acquire skills on critical aspects of building performance evaluation as a means of meeting the increasing demand for higher quality in education. The exploratory nature of this research clarifies the problems that need to be addressed in future studies and so raised a number of theoretical and conceptual issues that must be explored in the performance evaluation of educational buildings.